The Evolution of Illicit Flows Displacement and Convergence among Transnational Crime - Savona, Ernesto U.; Guerette, Rob T.; Aziani, Alberto (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book focuses on the displacement and convergence of transnational crimes in North Africa and in the area of the Mediterranean Sea, providing empirical analysis of human smuggling and of drug trafficking. It discusses the displacement of crime due to the exploitation of asymmetries in legislation, law enforcement, and other vulnerabilities. Using an innovative multimethodology, this volume describes the evolution of illicit flows related to human smuggling and trafficking of illicit goods. This approach helps to provide critical information such as traffickers' modi operandi, most exploited paths, and trafficked goods, that would not be achievable through more traditional methods. The Evolution of Illicit Flows will be a valuable resource for scholars and researchers of criminology and migration studies, as well as for policymakers and law enforcement working in transnational crimes and trafficking.
Chapter1. Introduction to "The Evolution of Illicit Flows: Displacement and Convergence among Transnational Crime" -- Part1. Concepts, Theories, History, and Perspectives -- Chapter2. The Displacement and Convergence of Transnational Crime Flows -- Chapter3. Trafficking in the Mediterranean World: A Historical Perspective -- Chapter4. Human Smuggling in the Mediterranean: A Comparative Analysis of the Central and Eastern Mediterranean Smuggling Routes -- Chapter5. Global Cocaine Flows, Geographical Displacement, and Crime Convergence -- Part2. Topical Analyses in Convergence and Displacement of Transnational Crimes -- Chapter6. Human Smuggling in North Africa: A Preliminary Exploration of Macro- and Micro-level Displacement Effects -- Chapter7. Displacement of human smuggling: An exploratory analysis of the effects of Law 82/2016 in Egypt -- Chapter8. Can Migration Flows be Controlled? The Effects of the Italian 2017-2018 Policy Against Illegal Immigration -- Chapter9. Does Human Smuggling Converge with Other Transnational Crimes in North Africa and the Mediterranean Area? -- Chapter10. Structure and Evolution of Drug Trafficking Networks in North Africa: The Impact of Rule of Law and Corruption -- Part3. Implications, Current Trends and Future Directions -- Chapter11. Human trafficking in the MENA region: trends and perspectives -- Chapter12. Future Directions in the Study of Displacement and Convergence among Transnational Crime Flows.
Keywords: Transnational crime; Organized crime; Transnational Crime; Organized Crime